Ulit, a shamanic healing ritual following the commemoration of the master of flowers, Tamway At Ampuq At Burak, in Palawan Highlands dialogism, polyglossy, plurivocality, spectral analysis - Revel, Nicole; Bolger, Deidre (2022)
To commemorate the Master of Flowers, the Pala’wan have an annual ritual making and drinking the Mead, Simbug. On June 26-27, 1983, in the large meeting-house of Taruwän in the Highlands of Mt. Mantalingahan, I witnessed the performance of Simbug.

Using ethnography of the spoken word and pragmatics, I propose to focus on the motions and speech acts of Panu, the Elder in the community. Followed by a healing session of a very young maiden, Rusi, in the presence of her mother Carmen, the plaintiff, Panu officiated as a shaman with Kälulut, his acolyte.

The verbal and co-verbal communication process, intertwining dialogues between the genuine Human Beings, and other Beings, Benevolents/Malevolents, living in the same realm are the focus of our attention. The discussion is conducted according to the rules of a negotiation, to come to an agreement and be successful in bringing back Rusi’s soul-double, her käruduwa.

If one considers that the sound production in singing or speaking contributes to the meaning of an utterance, it is important to take into account the acoustic features of the prosody, its intonation pattern, intensity, and tempo. A spectral analysis of Lumbaga, Bulikata, and Bisara will bring to light the prosodic features and quality of each of these three vocal styles and the semantic intentionality of the shaman in this multifaceted dialogue.
Keywords: Music & culture; Spectral Analysis; Vocal Music; Ritual music